2019
DOI: 10.1159/000502688
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Biomechanical and Histological Properties of the Abdominal Aorta of Diabetic Rats Exposed to Cigarette Smoke

Abstract: <b><i>Introduction:</i></b> In spite of the great relevance of abdominal aortic aneurysm, its etiopathogenesis is not fully understood. The biomechanical and histological study of the aortic wall may contribute to this elucidation. <b><i>Methods:</i></b> Seventy-five male Wistar rats were divided into 4 groups: control (CG), smoker (SG), diabetic (DG), and diabetic + smoker (DSG). The SG and DSG rats were exposed to cigarette smoke for 30 min/day, 5 days a week. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…One epidemiological study indicates that smoking history is the strongest factor associated with AAA progression [ 23 ]. Mechanistic research report that smoking promotes the degradation of collagen and elastin and consequent weakening of the arterial wall by highly expressed matrix metalloproteinase in aortic wall, finally leading to aortic aneurysm formation [ 24 ]. Although we observed that smoking had a robust association with the diameter of almost all segments apart from ascending aorta in the unadjusted model, the strength of this association could not be further demonstrated by fully adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One epidemiological study indicates that smoking history is the strongest factor associated with AAA progression [ 23 ]. Mechanistic research report that smoking promotes the degradation of collagen and elastin and consequent weakening of the arterial wall by highly expressed matrix metalloproteinase in aortic wall, finally leading to aortic aneurysm formation [ 24 ]. Although we observed that smoking had a robust association with the diameter of almost all segments apart from ascending aorta in the unadjusted model, the strength of this association could not be further demonstrated by fully adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, diabetes mellitus plays a protective role in dilated aortic diseases [ 8 , 27 ], characterized by the accumulation of collagen in the aortic wall and subsequent increases in matrix volume [ 28 ]. Interestingly, a rat study found that the total count of elastic fibers, fragmentation of the elastic lamina, pericellular matrix deposition, and cell loss/substitution in the tunica media were higher in the diabetic + smoker group (DSG) aorta than those in the smoker group (SG) aorta [ 24 ].The negative relationship between the presence of DM and aortic diameter was supported by a few other reports [ 8 , 15 ]. However, we found only that DM was inversely related with the diameters of annulus, mid and distal arch in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that exposure to e-cigarette is composed of 18 mg/ml of nicotine, 70% of propylene glycol, and 30% of vegetable glycerine for 1 h/day, 6 days a week for 4 weeks, resulting in cardiac fibrosis. Exposure to cigarette smoke for 30 minutes a day, 5 days/week for 16 weeks, causes changes in the aortic wall, such as the elastic fiber count, elastic lamina fragmentation, deposition of pericellular matrix, and cell substitution and loss in the tunica media significantly [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that one reader was not blinded to smoking status may have introduced a possible bias, but it was shown that excellent inter-rater agreement was achieved with the blinded reader. Second, THE estimates effective aortic stiffness only, which reflects elastic properties of the vessel wall and surrounding tissue and in part the prevailing arterial blood pressure at the time of measurement 29 31 . Additionally, with current technology THE does not allow determination of SWS throughout the cardiac cycle because the traveling pulse wave causes deflection of the aortic wall during systole precluding determination of systolic SWS within the vessel wall.…”
Section: Discussionmentioning
confidence: 99%